Risk-taking propensity and its influence on lexical decision performance: a comparative study of high- and low-risk groups - Sangyub Kim; Joonwoo Kim; Solbin Lee; Kichun Nam (Language and Cognition)
We examined the impact of risk-taking propensity on lexical decision performance in neurologically intact participants. Following the classification of participants into high- and low-risk-taking propensity groups using the Balloon Analogue Risk Task, we assessed lexical decision-making with behavioral responses (RTs, ACC), signal detection measures (hit, false alarm, miss, correct rejection) and qualitative processing using lexical variable effects (number of syllables, first syllable frequency, stem frequency, word frequency) between the groups. As a result, high-risk-taking individuals showed slower and less accurate word recognition, characterized by biased responses toward nonwords and words. However, both groups displayed similar patterns of lexical variable effects in word recognition, suggesting risk-taking propensity does not contribute to qualitative disparities in visual word recognition. These findings highlight the influential role of risk-taking propensity in shaping behavioral performance during lexical decision, emphasizing the need for further exploration of the intricate interplay between risk-taking behavior and lexical decision-making processes.